The effects of exercise on microRNA expression profiling in adipose tissue macrophages of mice - Qin, Fei; Huang, Wenbai; Qu, Chaoyi; Zhao, Lina; Du, Yunyu; Zhao, Tianyu; Feng, Yiwei; Zhao, Jiexiu (Frontiers in Immunology, 2024)
Background Exercise is recognized for its broad health benefits, influencing various physiological processes, including the behavior of adipose tissue macrophages (ATMs). While existing studies mainly associate ATM activity with obesity and metabolic syndrome, our study explores the impact of aerobic exercise on ATM microRNA expression profiling in a non-obese context, highlighting its general health-promoting mechanisms. Methods Sixty male C57BL/6 mice were randomly assigned to either a sedentary (S) or an exercise (E) group. The S group remained inactive, while the E group underwent a one-week treadmill adaptation, followed by an 8-week aerobic treadmill exercise protocol (60 min/day, 5 days/week, at 65%-75% VO2max). Post-training, glucose tolerance and the serum lipid levels were measured in mice subjected to both exercise and non-exercise conditions. ATMs harvested from visceral adipose tissues were analyzed and sorted using flow cytometer. To further investigate the effects of exercise in ATMs at the molecular level, miRNA microarray analysis was performed, followed by bioinformatic analysis. Results The 8-week regimen of moderate-intensity aerobic exercise ameliorated glucolipid metabolism and fostered a dynamic shift toward an M2 macrophage phenotype in the adipose tissue, independent of obesity. A total of 62 differentially expressed miRNAs were identified in ATMs of mice post-exercise. Notably, six miRNAs (miR-212-5p, miR-511-5p, miR-7b-5p, miR-142-3p, miR-1894-3p, and miR-31-5p) as well as their target gene were consistently altered and associated with macrophage polarization and metabolic regulation. Conclusion Our findings broaden the understanding of how exercise regulates ATM functions through significant changes in microRNA profiles, emphasizing its potential to enhance health and prevent chronic conditions. This study supports the application of aerobic exercise for its preventive effects on chronic diseases and underscores the importance of microRNA profiling in understanding the immune-modulatory impacts of exercise.